INFERTILITY PREVALENCE IN MAIN ETHNIC GROUPS OF URBAN AND RURAL POPULATIONS IN BURYAT REPUBLIC - Z. Yu. Darzhayev (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
Currently the infertility is one of the most important reproductive problems. In the previous epidemiological studies the infertility rate in the different regions of Eastern Siberia was shown as 12-21 %. This article shows the results of the epidemiological study of infertility in Buryat Republic. The questioning and medical examination was done in the random sampling of 1495 urban and 545 rural women of reproductive age. Some ethnic aspects of infertility were investigated too. It was estimated that in Russian population the number of fertile women is higher in rural regions compare to urban ones, in Buryats it doesn't depend on region. The rate of unknown fertility and primary infertility is significantly higher in rural women of both ethnic group. In Russians the frequency of secondary infertility is higher in urban region, but in Buryats it doesn't depend on region and is similar to the infertility rate in urban Russians.